Prohibition of Adultery in the Qur'an - Siti Nurkholisoh; Ahmad Soheh Mukarom (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the prohibition of adultery in the Qur'an. This research method is a literature study by collecting library sources, both primary and secondary with a content analysis approach. The results and discussion of this study include a general view of the meaning of adultery, punishment for people who commit adultery and the law of adultery in the Qur'an. The conclusion of this research is Allah SWT. strictly prohibits adultery because the act is a despicable act and is included in a major sin that has a bad impact on the perpetrator. People who commit adultery will be punished as Allah has said in the Qur'an. This study recommends that readers look for other references and study further about the discussion of adultery.